Efficient high-order spectral element discretizations for building block operators of CFD. (30th January 2020) - Huismann, Immo; Stiller, Jörg; Fröhlich, Jochen
Highlights: Efficient implementation of tensor-product operators for high-order spectralelement methods. Exploitation of parametrization, tailored unroll-jam and blocking of loops. 50% of the peak performance attained over a wide range of polynomial degrees. Benefit of new operator implementation demonstrated on combustion problem with 1: 72 · 10 9 mesh points. Abstract: High-order methods gain more and more attention in computational fluid dynamics. Among these, spectral element methods and discontinuous Galerkin methods introduce element-wise approximations by means of a polynomial basis. This leads to a small number of operators consuming a large portion of the runtime of CFD applications. The present paper addresses tensor-product bases which are among the most frequent in these applications. Various implementations are developed and performance tests conducted for the interpolation operator, the Helmholtz operator, and the fast diagonalization operator. For each, up to 50% of the peak performance is attained, beating matrix-matrix multiplication for every polynomial degree relevant for simulations. This extremely high efficiency of the method developed is then demonstrated on a combustion problem with 1.72 · 10 9 mesh points.